Polymers, catalysts and nanostructures a hybrid approach to biomolecule detection - Frith, Kelly-Anne (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2009)
The main goals in electroanalytical sensing are towards improved sensitivity and selectivity, or specificity, of an analyte. There are several approaches to achieving these goals with the main approach being modification of an electrode surface with synthetic or natural catalysts (enzymes), polymers and also utilisation of nanostructured materials. At present, there is a strong movement towards hybrid sensing which couple different properties of two or more surface modification approaches. In this thesis, a range of these surface modifications were explored for analysis and detection of two main analytes: the amino acid, tryptophan (Trp); and, the neurotransmitter, dopamine (DA). Specifically, this thesis aimed to utilise these methods to enhance the sensitivity and selectivity for Trp over an interferent, the indoleamine, melatonin (Mel); and, DA over the vitamin, ascorbic acid (AA). For Trp detection, immobilisation of an enzyme, Tryptophanase (Trpase) resulted in poor selectivity for the analyte. However, enhanced sensitivity and selectivity was achieved through pH manipulation of the electrolyte medium at a Nafion®-modified electrode surface for both Trp and Mel. At pH 3.0, the Mel and Trp anodic peak potentials were sufficiently resolved allowing for an LOD of 1.60 and 1.62 nM,respectively, and permitting the accurate analysis of Trp in a dietary supplement containing Mel. Multi-walled carbon nanotubes (MWCNTs) suspended in Nafion® exhibited further increases in the signal responses of these analytes at pH 3.0 and 7.4 with minimal change in the resolution of the anodic peaks. A lower sensitivity was, therefore, observed at the Nafion® and MWCNT modified electrode compared to the Nafion®-modified electrode at pH 3.0 with LODs of 0.59 and 0.80 nM exhibited for Trp and Mel, respectively. Enhanced selectivity for Trp in the presence of Mel can be achieved with MWCNTs in the presence of metallotetrasulphonated phthalocyanines (MTSPcs) particularly at pH 3.0, owing to cation exchange effects. However, the lack of sensitivity towards Trp, and even Mel, at this CoTSPc and MWCNT modified electrode remains a drawback. For DA, detection at the MWCNT and Nafion® surface resulted in improved sensitivity over that of both the bare electrode (613.0 nM) and the Nafion® modified electrode (1045.1 nM) with a calculated LOD of 133.9 nM at this layer. Furthermore, improvements in the selectivity of DA were achieved at the Nafion® and MWCNT modified electrode as exclusion of AA (150 μM) was achieved. At the MWCNT and CoTSPc surface, AA was excluded up to 130 μM with sensitivity for DA extending as low as 14.3 nM, far greater than observed for Trp and Mel. These concentrations are well within physiological concentration ranges and represent the most significant solution yet in terms of AA exclusion and enhanced sensitivity for DA. An examination of the surface layering by impedance spectroscopy and atomic force microscopy indicates that the success of the hybrid sensor utilising CoTSPc and MWCNTs lay in improved dispersion of MWCNTs and improved electron transfer kinetics, facilitated by the net charge of the materials present. This thesis, thus, showed the utility of a judicious selection of synthetic and biological catalysts, polymers and carbon nanomaterials towards a hybrid approach to the electrochemical sensing of Trp, Mel, DA and AA with focus on sensitivity and selectivity of these analytes.
Keywords: Polymers; Nanostructured materials; Biomolecules; Tryptophan; Melatonin; Electrodes; Electrochemistry; Tryptophan oxygenase